EGMR 23378/15 vom 30. Mai 2017 , CASE OF A.I. v. SWITZERLAND - [Polish Translation] by the Polish Supreme Administrative Court - Hudoc Ch (2017)
Remainder inadmissible (Art. 35) Admissibility criteria;(Art. 35-3-a) Manifestly ill-founded;Violation of Article 2 - Right to life (Article 2 - Expulsion) (Conditional) (Sudan);Violation of Article 3 - Prohibition of torture (Article 3 - Expulsion) (Conditional) (Sudan); Violation: 2;3